1984
DOI: 10.1159/000233617
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Immunological Effects of Chronic Antigen Exposure in Immunized Guinea Pigs

Abstract: Antigenic tolerance was induced in previously sensitized guinea pigs by challenging with ovalbumin (OA) aerosol 1 h/day, 5 days/week for 6 weeks. Reactivity was assessed visually and by lung mechanics. Sera from tolerant and sensitized animals showed comparable titers of antigen-specific antibody by passive cutaneous anaphylaxis with 6-hour, 4-day (heated serum) and 7-day sensitizations. In vitro contractile responses of airway smooth muscle revealed comparable histamine responses in sensitized and tolerant gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Deterioration of EAR observed especially in the OA repetitive inhalation group is not likely to be proportional to the serum levels of 71 or IgE in both cases of the present sensitization methods in accordance with another report (23). Andrew et al (23) suggested that the desensitization in EAR is due to the decreased releasability of histamine in low concentrations of challenging antigen.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Deterioration of EAR observed especially in the OA repetitive inhalation group is not likely to be proportional to the serum levels of 71 or IgE in both cases of the present sensitization methods in accordance with another report (23). Andrew et al (23) suggested that the desensitization in EAR is due to the decreased releasability of histamine in low concentrations of challenging antigen.…”
Section: Discussionsupporting
confidence: 88%
“…Andrew et al (23) suggested that the desensitization in EAR is due to the decreased releasability of histamine in low concentrations of challenging antigen. In the present experiments, mepyramine was used for prevention of sudden death, so that the possibility can be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that the amounts of chemical mediators released from the mast cells in response to the 14th antigen challenge are enhanced at the 2nd day but not the 7th day after the 13th antigen challenge. However, when sensitized guinea pigs were chronically exposed to aerosolized antigen, the amount of histamine anaphylactically released from isolated lung fragments was apparently decreased (31). Thus, it is unlikely that potentiation of anaphylactic production and / or release of chemical mediators from mast cells is induced on day 2 but not day 7.…”
Section: Discussionmentioning
confidence: 99%